Last breath [videorecording (DVD)] - Parkinson, Alex; LaFortune, Mitchell; Brooks, David, 1969-; Harrelson, Woody; Liu, Simu, 1989-; Cole, Finn, 1995-; Curtis, Cliff, 1968-; Leonard-Morgan, Paul; Matthews, Nick (Universal, 2025)
Seasoned deep-sea divers battle the raging elements to rescue their crewmate trapped hundreds of feet below the ocean's surface. Based on a true story, the crew use teamwork, resilience, and a race against time to do the impossible.